Quality and shelf life of minimally-processed litchi fruit - Putkrong Phanumong (2018)
Quality and shelf life of sanitized peeled litchi arils of three cultivars, 'Honghuay', 'Gimjeng' and 'Jugkapat', were studied. The peeled and deseeded litchi arils were sanitized with 50 mg/L of peroxyacetic acid (PAA) solutions for 1 min. Subsequently, they were drained, packed in a polystyrene clamshell box and analyzed during storage at 4±1°C for 12 days. Firmness and lightness (L*) values of the arils decreased and juice leakage increased during storage. The pH, total soluble solids and total titratable acidity during storage changed slightly. Ascorbic acid contents decreased after sanitation and during storage. Sanitation with PAA delayed growth of all bacteria, yeast and molds within the specified microbial criteria. The appearance of the litchi arils was not translucent, however, with the texture softening around the cut area of the stem-end. Based on organoleptic evaluation, the shelf life of peeled litchi arils was 5 days at 4±1°C. In addition, the 'Jugkapat' cultivar was the most appropriate candidate for minimally-processed produce, because of its larger fruit size, ease of deseeding, the absence of brown color on the internal surface of the arils and the high ascorbic acid content.